2008
DOI: 10.1099/mic.0.2008/019828-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon source availability and growth phase on expression of Corynebacterium glutamicum genes involved in the tricarboxylic acid cycle and glyoxylate bypass

Abstract: The effect of different carbon sources on the expression of tricarboxylic acid (TCA) cycle genes, along with glyoxylate bypass genes, in Corynebacterium glutamicum was determined. All TCA cycle genes were coordinately expressed in medium containing acetate. Growth in the presence of acetate gave rise to abundant expression of most TCA cycle genes, with the level of gltA transcript being the highest. However, when the cells entered the stationary phase triggered by acetate exhaustion, all genes were repressed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 60 publications
3
44
2
Order By: Relevance
“…Additional studies showed that GlxR is a global regulator with dual functionality that is predicted to directly regulate about 14% of the annotated C. glutamicum genes (66)(67)(68)(69). Binding of GlxR to several of its target promoters was shown to be strictly dependent on the presence of cAMP in vitro (40,41,65,68,(70)(71)(72)(73). The intracellular concentration of cAMP in C. glutamicum seems to vary with the carbon source and the growth phase of the culture, as it is, for instance, high when cells are grown on glucose and low when cells are grown on acetate medium (65,74).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies showed that GlxR is a global regulator with dual functionality that is predicted to directly regulate about 14% of the annotated C. glutamicum genes (66)(67)(68)(69). Binding of GlxR to several of its target promoters was shown to be strictly dependent on the presence of cAMP in vitro (40,41,65,68,(70)(71)(72)(73). The intracellular concentration of cAMP in C. glutamicum seems to vary with the carbon source and the growth phase of the culture, as it is, for instance, high when cells are grown on glucose and low when cells are grown on acetate medium (65,74).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether GlxR acts as a transcriptional activator or repressor of most of these genes is difficult to evaluate, not only because construction of a glxR deletion mutant is difficult but because any mutant that has been successfully constructed shows severe growth defects (41,49,59,79). The role of GlxR has been assessed only by in vitro binding assays and overexpression studies in vivo (14,32,33,40,49), although GlxRdependent repression of genes involved in the glyoxylate pathway and glutamate uptake system was recently confirmed by experiments using a glxR mutant (59). Therefore, the physiological function of and environmental signal(s) sensed by GlxR remain poorly understood.…”
mentioning
confidence: 99%
“…First characterized as a factor repressing the promoter activity of a gene coding for a glyoxylate pathway enzyme (41), GlxR is involved in the regulation of several other genes. Like E. coli CRP, it binds to the consensus site 5Ј-TGTGA-N 6 -TCACA-3Ј in a cAMP-dependent manner in vitro (32,33,40,41,49). In silico analyses have detected more than 200 potential binding sites for GlxR in the C. glutamicum genome, and binding to 72 of the sites has been verified by in vitro binding assays, revealing that the regulon includes genes for carbon metabolism, nitrogen metabolism, respiration, resuscitation, cell wall formation, and cell division (42,43).…”
mentioning
confidence: 99%
“…In the setting of high airway glucose concentrations, excessive glucose may serve as a steady source of both carbon and energy for proliferating infectious bacteria, creating an environment within the lung conducive to bacterial growth and endurance (11). Recent in vivo animal data have demonstrated that airway glucose control is essential to maintaining airway sterility (29).…”
Section: Discussionmentioning
confidence: 99%